Variações da estrutura a termo de taxa de juros e mudanças na imunização de carteiras com análise de componente principal - Kohatsu, Marcelo Yoshimatsu (Universidade Federal de São Carlos, 2014)
The purpose of this dissertation is investigating changes on the immunized portfolios by the analytic method of principal components analysis from an inversion movement of the term structure of interest rates. In 2012, the one year yield curve had short term's interest rate higher than long term's interest rate, featuring a decrescent profile behavior. In December 2012, the structure shape changed and became firstly flat to become, later, a positively sloped curve. The method of immunization with analysis of principal component uses a structure by retroactive term for the calculation of the facts towards the greatest variance. In this dissertation we verify that the use of a decrescent historic of the structure on term for the calculation of the components did not present inconsistencies in the immunization of the portfolio in the period that the structure on term was becoming itself crescent.
Variations in the term structure interest and changes in the portfolios with principal components analysis.
Keywords: política monetária; taxas de juros; monetary policy, interest rates; CIENCIAS SOCIAIS APLICADAS::ECONOMIA